-(7-4x)=-5x-(-8)

Simple and best practice solution for -(7-4x)=-5x-(-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7-4x)=-5x-(-8) equation:



-(7-4x)=-5x-(-8)
We move all terms to the left:
-(7-4x)-(-5x-(-8))=0
We add all the numbers together, and all the variables
-(-4x+7)-(-5x-(-8))=0
We get rid of parentheses
4x-(-5x-(-8))-7=0
We calculate terms in parentheses: -(-5x-(-8)), so:
-5x-(-8)
We add all the numbers together, and all the variables
-5x+8
Back to the equation:
-(-5x+8)
We get rid of parentheses
4x+5x-8-7=0
We add all the numbers together, and all the variables
9x-15=0
We move all terms containing x to the left, all other terms to the right
9x=15
x=15/9
x=1+2/3

See similar equations:

| 6=y/192 | | -1=(-8n+3.9) | | x-2+2x=5+3x-7 | | 34+w/2=-11 | | 25+7x=-17 | | 2p-4=2(p+1) | | c+7=9-5c | | k^2-2k-63=0 | | 14x+2=9x−39x−3 | | 16+1-8h-h=-5-3 | | 6(5x-6)=-6 | | 3(3x-2)=2(x+4) | | 180=-9x | | n=3n-27 | | 8/x–10=10+20 | | y+2.3=2.5 | | 4(-4+7x)=-100 | | 9+2y=1+6y | | V(a)=(8+-2×)(6+-2×)(a) | | (5x–21)+(7x–39)=180 | | 5(x+4)=7x–26 | | x-7=x=19 | | 2(4-3x)=3(3x+4) | | 12n-12=180 | | -12=6-8x | | 2(34-3x)=3(3x+4) | | 10+-2v=-5v-50 | | 1-14x=14+3x+11 | | -3(3+6x)=135 | | 21x-20-x2=0 | | 3(2x+1=5x+7 | | X+m=16 |

Equations solver categories